Is Promiscuous CALB a Good Scaffold for Designing New Epoxidases? - Isabel Bordes; José Recatalá; Katarzyna Świderek; Vicent Moliner (Molecules, 2015)
Candida Antarctica lipase B (CALB) is a well-known enzyme, especially because of its promiscuous activity. Due to its properties, CALB was widely used as a benchmark for designing new catalysts for important organic reactions. The active site of CALB is very similar to that of soluble epoxide hydrolase (sEH) formed by a nucleophile-histidine-acid catalytic triad and an oxyanion hole typical for molecular structures derived from processes of α/β hydrolases. In this work we are exploring these similarities and proposing a Ser105Asp variant of CALB as a new catalyst for epoxide hydrolysis. In particular, the hydrolysis of the trans-diphenylpropene oxide (t-DPPO) is studied by means of quantum cluster models mimicking the active site of both enzymes. Our results, based on semi-empirical and DFT calculations, suggest that mutant Ser105Asp CALB is a good protein scaffold to be used for the bio-synthesis of chiral compounds.